Producing biochar using a custom designed Top-lit Updraft (TLUD) gasifier - Jehangir H. Bhadha; Stephen Jennewein; Julio Sanchez; Timothy A. Lang (EDIS)
Biochar can be produced in a wide variety of ways; some are complex, while others are relatively simple. Researchers at the University of Florida Everglades Research and Education Center in Belle Glade, FL, designed and built a top-lit updraft (TLUD) gasifier that can generate biochar from locally acquired feedstock. This 4-page fact sheet describes its design and evaluates the biochar recovery of four locally available feedstocks. Written by Jehangir H. Bhadha, Stephen Jennewein, Julio Sanchez, and Timothy A. Lang, and published by the UF Department of Soil and Water Science, September 2014.